Liver Disorders in Type 2 Diabetes Mellitus - Suzanna Ndraha; Marshell Tendean; Fendra Wician; Henny Tanadi Tan; Helena Yap (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: Patients with type 2 diabetes mellitus (T2DM) are frequently diagnosed with some abnormal liver features. These liver abnormalities are suggested to be correlated with insulin resistance. The aim of thisstudy was to evaluate liver abnormalities and fasting insulin levels in patients with T2DM.Method: This study was conducted in Koja Hospital from February to July 2013. Study design was analytical study. Data for sex, age, complication, body mass index (BMI), liver function, liver enzyme, and fasting insulinlevel were collected. Univariate and bivariate statistical analyses were done using SPSS 20.Results: Twenty eight patients were included in this study, 71.43% of them were female. The age group of 40-60 years was the highest among the patients (64.28%). Highest complication was neuropathy, BMI of mostpatients were obese. Liver abnormalities were documented in 35.8% patients, liver enzyme increased in 21.4% patients. Non alcoholic fatty liver disease (NAFLD) were noted in 46.6% patients, and one patient was positive for hepatitis B. Mean fasting insulin in T2DM with NAFLD were higher than in T2DM without NAFLD. However, it was not statistically significant (40.08 ± 36.8 μU/mL vs. 54.3 ± 37.1 μU/mL; p = 0.27).Conclusion: Liver abnormalities found in T2DM patients were elevated liver enzyme, decreased albumin and increased of bilirubin. Through ultrasound, NAFLD and liver cirrhosis were found. Fasting insulin levelwas higher in T2DM with NAFLD but it was not statistically significant.Keywords: type 2 diabetes mellitus, non alcoholic steato-hepatitis, fasting insulin